Evaluating the Extent of Commitment of Commercial Banks Operating in Damascus to the Strategic Decision Entrances (Journal of Hama University, 2022)
This study aims to identify the extent of the commitment of commercial banks operating in the city of Damascus to the strategic decision entrances, in order to develop the work systems applicable in those banks and to reach a new pattern in administrative work that guarantees their distinction and success, and this study was applied to all operating public and private commercial banks. In the city of Damascus, the researcher used the descriptive and analytical approach and used the questionnaire tool to collect information, and then perform the appropriate statistical analysis using the methods of statistical treatment included in the program (SPSS24). The sample of the study reached (269) male and female workers.The results of the study showed that there are statistically significant differences in the perception of the members of the surveyed sample of the level of commitment of commercial banks to the strategic decision entrances due to the variable of administrative dependency and in favor of private banks, the scientific qualification variable in favor of workers with higher academic qualifications, and the variable number of years of experience in favor of workers with more years of experience, The job level variable and in favor of the higher career level.